In vitro study of trileaflet polytetrafluoroethylene conduit and its valve-in-valve transformation. (3rd January 2020) - Chang, Te-I; Hsu, Kang-Hong; Luo, Chi-Wen; Yen, Jen-Hong; Lu, Po-Chien; Chang, Chung-I
Abstract: : OBJECTIVES: Handmade trileaflet expanded polytetrafluoroethylene valved conduit developed using the flip-over method has been tailored for pulmonary valve reconstruction with satisfactory outcomes. We investigated the in vitro performance of the valve design in a mock circulatory system with various conduit sizes. In our study, the design was transformed into a transcatheter stent graft system which could fit in original valved conduits in a valve-in-valve fashion. METHODS: Five different sizes of valved polytetrafluoroethylene vascular grafts (16, 18, 20, 22 and 24 mm) were mounted onto a mock circulatory system with a prism window for direct leaflets motion observation. Transvalvular pressure gradients were recorded using pressure transducers. Mean and instant flows were determined via a rotameter and a flowmeter. Similar flip-over trileaflet valve design was then carried out in 3 available stent graft sizes (23, 26 and 28.5 mm, Gore aortic extender), which were deployed inside the valved conduits. RESULTS: Peak pressure gradient across 5 different sized graft valves, in their appropriate flow setting (2.0, 2.5 and 5.0 l/min), ranged from 4.7 to 13.2 mmHg. No significant valve regurgitation was noted (regurgitant fraction: 1.6–4.9%) in all valve sizes and combinations. Three sizes of the trileaflet-valved stent grafts were implanted in the 4 sizes of valved conduits except for the 16-mm conduit. Peak pressure gradient increase after valved-stent graft-in-valved-conduit setting was <10 mmHg in all 4 conduits. CONCLUSIONS: The study showed excellent in vitro performance of trileaflet polytetrafluoroethylene valved conduits. Its valved stent graft transformation provided data which may serve as a reference for transcatheter valve-in-valve research in the future.